Physiological indices and production of sesame under salt stress and nitrate/ammonium proportions (Bioscience Journal, 2017)
In semi-arid regions, the occurrence of water with high concentration of salts is common, which compromises the growth and consequently the production of crops. Thus, this study aimed to evaluate the gas exchanges and production of sesame, cv. CNPA G3, irrigated with saline water and fertilized with different proportions of nitrate and ammonium, in an experiment conducted using lysimeters in a greenhouse in the municipality of Campina Grande-PB, Brazil. The treatments were arranged in randomized blocks and analyzed in a 5 x 5 factorial scheme, with three replicates, relative to five levels of electrical conductivity of the irrigation water - ECw (0.6, 1.2, 1.8, 2.4 and 3.0 dS m-1) and five proportions of nitrate/ammonium - NO3-/NH4+ (200/0, 150/50, 100/100, 50/150 and 0/200 mg of N kg-1 of soil). Irrigation with water of salinity level higher than 0.6 dS m-1 promoted negative effect on gas exchanges and production components of the sesame cv. CNPA G3. Fertilization with N exclusively in the form of NH4+ promoted increment in CO2 concentration and reduction in its assimilation rate and instantaneous carboxylation efficiency. The highest rate of CO2 assimilation, transpiration and instantaneous carboxylation efficiency were obtained when the plants were irrigated with water of 0.6 dS m-1 and fertilization with 200/0 of NO3-/NH4+. Increasing levels of water salinity promoted a decrease in the total seed mass, regardless of the proportion of NO3-/NH4+. The sesame cv. CNPA G3 is classified as sensitive to salt stress from the electrical conductivity of water of 0.6 dS m-1.